A new PD based robust control method for the robot joint module. (December 2021) - Zhen, ShengChao; Peng, Xin; Liu, XiaoLi; Li, HongMei; Chen, Ye-Hwa
Highlights: A new robust control is proposed for the robot joint module with uncertainties. The robust control is PD based and inherits model-based control. The uncertainties and external disturbances considered in system are bounded. The design flow and parameter selection of the controller are given. Variable-load experiments are conducted to verify the effectiveness. Abstract: In order to reduce the impact of load and system parameter changes on the dynamic performance of the robot joint module, we propose a PD based robust control method, which also inherits the traditional model-based control, with convenient realization and actual effectiveness. The controller is composed of two parts: one is a nominal controller designed based on the dynamic model to stabilize the nominal mechanical system, the other part is a robust controller based on the Lyapunov method to eliminate the impact of uncertainty on tracking performance. Based on the actual joint module platform and the rapid controller prototype CSPACE, we simulated and carried out experimental verification with two friction models. Theoretical analysis and experimental results show that the controller can significantly improve the dynamic performance of the robot joint module system.